Off-balance Sheet Transactions in Financial Statements - Chluska, Jolanta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The article identifies areas of financial statements that are particularly sensitive to the impact of off-balance sheet transactions.Research Design & Methods: An analysis of the subject literature, legal acts and examples of practical identification of the effects of off-balance transactions were applied.Findings: The article looks at the important conditions of the potential control over reporting information, which is not always the result of the balance sheet policy and may be a tool for manipulating an entity’s image in the financial statements.Implications / Recommendations: Economic entities conclude various contracts during their operations. Some may have a particular impact on the entity’s image in the financial statements and the condition of the entity. The effects of such agreements may be short- or long-term.Contribution: The article presents the essence of off-balance transactions and their impact on the entity’s image in the financial statements. Analysis of the subject literature and financial statements prompts the research hypothesis that off-balance sheet transactions can significantly change the entity’s view in the financial statements.